2021
DOI: 10.3389/fnins.2021.644543
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Regional Homogeneity in Preschool Boys With Autism Spectrum Disorders

Abstract: ObjectivesThe study was aimed at investigating the alterations of local spontaneous brain activity in preschool boys with autism spectrum disorders (ASD).MethodsBased on regional homogeneity (ReHo), the acquired resting state functional magnetic resonance imaging (fMRI) data sets, which included 86 boys with ASD and 54 typically developing (TD) boys, were used to detect regional brain activity. Pearson correlation analysis was used to study the relationship between abnormal ReHo value and the Childhood Autism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
(48 reference statements)
1
11
1
Order By: Relevance
“…From the perspective of the overall analysis of the whole-brain function of prepubertal ASD patients, unlike the research results about ASD in the infant stage ( Redcay and Courchesne, 2008 ), preschool stage ( Lan et al, 2021 ), and adolescent period ( Shukla et al, 2010 ), we did not find any regions that had increased brain activity. This is similar to brain development.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…From the perspective of the overall analysis of the whole-brain function of prepubertal ASD patients, unlike the research results about ASD in the infant stage ( Redcay and Courchesne, 2008 ), preschool stage ( Lan et al, 2021 ), and adolescent period ( Shukla et al, 2010 ), we did not find any regions that had increased brain activity. This is similar to brain development.…”
Section: Discussioncontrasting
confidence: 97%
“…The LG has been suggested to be involved in visual recognition and episodic memory consolidation ( Kukolja et al, 2016 ) and has been considered to play a role in the process of perceiving the surrounding environment ( Bischof and Bassetti, 2004 ). However, in a study of preschool ( Lan et al, 2021 ) and adolescent children ( Shukla et al, 2010 ) with ASD, decreased ReHo in the left LG was not found. Furthermore, the decrease in synchronization of neural activity in the left LG that we found had a negative correlation with the ADOS social affect score.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The brain regions with abnormal spontaneous brain activity in previous studies of preschool boys with ASD ( Lan et al, 2021 ) were defined as the ROI, with a radius of 6 mm. These five brain regions were the right calcarine (9, −90, 3), right mOFC (6, 51, −9), left MTG (−42, −48, 9), left AG (−42, −57, 27), and left IFG operc (−39, 3, 21).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study on preschool boys with ASD using regional homogeneity analysis, we found that the right medial orbital frontal cortex (mOFC, which explains the ASD’s repetitive stereotyped behavior), the opercular part of the left inferior frontal gyrus (IFG operc), the left middle temporal gyrus (MTG), and the left angular gyrus (AG, which can explain social language development defect) had abnormal spontaneous brain activity, as well as the right calcarine, a part of the primary visual cortex ( Lan et al, 2021 ). Repetitive and rigid behaviors and social language development disorders are undoubtedly the most obvious clinical symptoms in ASD, and the strengthening of visual ability also seems to be important in the early stage of ASD.…”
Section: Introductionmentioning
confidence: 99%